Prevalence and Incidence of Non-alcohol Fatty Liver Disease in Chronic Hepatitis B Population in Southeast China: A Community-Based Study - Zheng, Yang; Xu, Kaijin; Hu, Haiyang; Draz, Mohamed S.; Wu, Wei; Li, Lanjuan (Frontiers in Medicine, 2021)
Background: To investigate the prevalence and incidence of non-alcohol fatty liver disease (NAFLD) in a community-based chronic hepatitis B (CHB) population from Southeast China and evaluate the association between NAFLD and metabolic factors, viral factors, and underlying chronic diseases. Methods: CHB patients were recruited in 2012 and followed up from 2017 to 2019 in Zhejiang, China. NAFLD prevalence of the last visit and NAFLD incidence were calculated. Potential risk factors, including metabolic and viral factors, were also evaluated using Logistic or Cox regression models. Results: NAFLD prevalence of the last visit in 2019 was estimated at 26.76%. Waist circumference, body mass index (BMI), triglyceride (TG), low-density lipoprotein (LDL), diabetes mellitus (DM) were found as associated factors. In subgroups analysis, HBV infection types were also identified as a risk factor in the non-diabetic population. HBeAg negative hepatitis and immunotolerant had lower NAFLD prevalence than past CHB infection. NAFLD incidence was estimated at 22.63/1000 person-years after 1634.74 person-years of follow-up. Waist circumference, TG, LDL, alkaline phosphatase (ALP) were identified as associated factors. Conclusion: The NAFLD prevalence and incidence in our study were slightly lower than previous reports from East Asia. Health education and healthy living habits were extremely important in reducing the NAFLD burden. Metabolic factors, history of diabetes mellitus, and viral factors were associated with NAFLD in chronic hepatitis B patients.